2001
DOI: 10.1002/1529-0131(200101)44:1<231::aid-anr30>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of desensitization to allopurinol following cutaneous reactions

Abstract: Objective To evaluate the long‐term efficacy and safety of slow oral desensitization in the management of patients with hyperuricemia and allopurinol‐induced maculopapular eruptions. Methods A retrospective evaluation of an oral desensitization regimen using gradual dosage‐escalation of allopurinol in 32 patients (30 with gout and 2 with chronic lymphocytic leukemia) whose therapy was interrupted because of a pruritic cutaneous reaction to the drug. Results Twenty‐one men and 11 women with a mean age of 63 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
0
5

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(68 citation statements)
references
References 49 publications
1
58
0
5
Order By: Relevance
“…16 T-cell-mediated hypersensitivity is, however, a major mechanism in delayed hypersensitivity reaction, which requires dozens of days to increase the dose step by step for tolerance induction. 30 In the current study we used a 28-day slow tolerance induction protocol adapted from the desensitization protocol described by Fam et al, 21 which showed successful tolerance induction in 78% of hyperuricemic patients with allopurinol-induced maculopapular eruption, and borrowed the idea from the fact that allopurinol administration by a slow desensitization protocol could avoid activating already existing memory cells into effector cells. We speculated that slow, gradual escalation of the drug based on a tolerance induction protocol might help to skip the generation of effector and memory T cells, although the existence of those cells was not verified in the study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 T-cell-mediated hypersensitivity is, however, a major mechanism in delayed hypersensitivity reaction, which requires dozens of days to increase the dose step by step for tolerance induction. 30 In the current study we used a 28-day slow tolerance induction protocol adapted from the desensitization protocol described by Fam et al, 21 which showed successful tolerance induction in 78% of hyperuricemic patients with allopurinol-induced maculopapular eruption, and borrowed the idea from the fact that allopurinol administration by a slow desensitization protocol could avoid activating already existing memory cells into effector cells. We speculated that slow, gradual escalation of the drug based on a tolerance induction protocol might help to skip the generation of effector and memory T cells, although the existence of those cells was not verified in the study.…”
Section: Discussionmentioning
confidence: 99%
“…Patients who were HLA-B*58:01-positive based on the HLA screening test were prescribed allopurinol following a 28-day schedule for the slow oral tolerance induction protocol 21 (Supplementary Table S1 online). The allopurinol tolerance induction protocol used in this study was originally made for patients who had allopurinol-induced maculopapular eruptions.…”
Section: Allopurinol Tolerance Induction Protocolmentioning
confidence: 99%
“…Allopurinol is started at a very low dose and then escalated very slowly every few days, increasing up to 100 mg daily over a 1-month period. 16 Preventing ULT-induced acute attacksPrecipitation or worsening of an acute attack of gout can occur following initiation …”
Section: Initiation and Titration Of Ult -mentioning
confidence: 99%
“…Our experience confirms the validity of this procedure, which was managed on an outpatient basis, not involving hospitalization. A similar approach may be performed in cases of skin reactions after allopurinol administration 4 .…”
Section: Successful Desensitization To Hydroxychloroquine (Hcq) Was Rmentioning
confidence: 99%